Evaluation of HbxRBC product as a screening method in sickle cell Anemia - Jawarkar, Ashish; Agrawal, Aakanksha (Tropical Journal of Pathology and Microbiology, 2019)
Background: India has been ranked the second worst affected country in terms of predicted SCD births. In developed countries, new-born screening programs have been established to ensure early diagnosis, but in most developing countries, screening is not performed, and the diagnosis is often delayed. Aim of present study was to analyse the effectiveness of Hb*RBC product as a screening tool. Methods: In the present study, blood from 200 patients suspected to have Sickle cell hemoglobinopathies was analysed and subjected it to Sickling screening test. All positive cases were subjected to HPLC to separate constituent haemoglobins and CBC analysis was done to check RBC indices. Hb*RBC product was analysed. Results: Analysis of Hb*RBC product revealed that there was a statistically significant difference in values between controls and disease patients. Hb*RBC product had good sensitivity and specificity in predicting sickle cell disease. Conclusions: Hb*RBC<45 was sensitive and specific predictor of sickle cell disease and can be used as a screening tool. Patients with this finding should be further subjected to specific tests like Hb electrophoresis for confirmation.